Let's Reset The Clock: Family Footage to Remediate Distance Created by Mourning - Gomis, Elsa (img journal, 2020)
From Sherlock Jr. (1924) by Buster Keaton, to Laura by Shuji Terayama (1974), or Videodrome by David Cronenberg (1983), to more recent to Leto by Kirill Serebrennikov (2018), experimental and mainstream cinema has explored crossings through the screen to attempt erasing borders between the viewers and those represented. Let’s Reset the Clock (from French On va remettre les pendules à l’heure), is a two-and-a-half minute colour video that I chose to inscribed in this tradition. In this artwork, split screen visual process is used to remove distances, in order to put two characters –I, the author, and my own grandmother– face to face. As the latter has passed away, Let’s Reset the Clock, constitutes an attempt to remediate distances created by the mourning and a reflection about the way images can bridge those separated by space and by the time.